Internal versus external group conflicts. (7th July 2022) - Fog, Agner
Abstract: A group in intergroup conflict needs to overcome the collective action problem in order to defend itself against an external enemy. This leads to increasing complexity that cannot be adequately covered by just scaling up the model of intragroup conflicts. Research on cultural evolution and evolutionary psychology shows that external conflict has profound effects on group organization.